2015
DOI: 10.1139/cjm-2015-0334
|View full text |Cite
|
Sign up to set email alerts
|

Episodic adaptive diversification of classical swine fever virus RNA-dependent RNA polymerase NS5B

Abstract: Classical swine fever virus (CSFV) is the pathogen that causes a highly infectious disease of pigs and has led to disastrous losses to pig farms and related industries. The RNA-dependent RNA polymerase (RdRp) NS5B is a central component of the replicase complex (RC) in some single-stranded RNA viruses, including CSFV. On the basis of genetic variation, the CSFV RdRps could be clearly divided into 2 major groups and a minor group, which is consistent with the phylogenetic relationships and virulence diversifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…[41][42][43] Notably, in classical swine fever virus of the genus Pestivirus, it has been reported that adaptive diversification has occurred on the RdRp NS5B between two major groups, which could be relevant to their virulence diversity. 44 In hepatitis C virus of the genus Hepacivirus, a number of adaptive changes have also taken place on the polymerase NS5B with the split of the predominant subtypes 1a and 1b. 45 Thus, the accumulated results implied that the changes on the NS5 proteins frequently constitute a genetic signature relevant to the biological diversity and (or) large-scale dissemination of the viruses in the family Flaviviridae.…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43] Notably, in classical swine fever virus of the genus Pestivirus, it has been reported that adaptive diversification has occurred on the RdRp NS5B between two major groups, which could be relevant to their virulence diversity. 44 In hepatitis C virus of the genus Hepacivirus, a number of adaptive changes have also taken place on the polymerase NS5B with the split of the predominant subtypes 1a and 1b. 45 Thus, the accumulated results implied that the changes on the NS5 proteins frequently constitute a genetic signature relevant to the biological diversity and (or) large-scale dissemination of the viruses in the family Flaviviridae.…”
Section: Discussionmentioning
confidence: 99%